Bi‐directional actions of dehydroepiandrosterone and aggression in female Siberian hamsters. Issue 2 (24th December 2015) - Rendon, Nikki M.; Demas, Gregory E.
ABSTRACT: There is a well‐established positive relationship between gonadal steroids and aggression. In some seasonally breeding species, however, aggression often persists or is increased during short "winter‐like" days when the gonads are regressed and circulating levels of gonadal steroids are relatively low. Although the mechanisms underlying short‐day increases in aggression are not fully known, the adrenal androgen dehydroepiandrosterone (DHEA) has been suggested as an alternative neuroendocrine mechanism regulating seasonal aggression. We used two complementary experimental approaches to examine the bi‐directional actions of DHEA and aggression in female Siberian hamsters, a seasonal rodent that displays increased aggression concomitant with elevated circulating DHEA in short days. In Experiment 1, we examined the effects of aggressive interactions on DHEA concentrations before and after an aggressive encounter in long‐ and short‐day hamsters. Serum DHEA was altered in a photoperiod‐dependent manner, with decreased DHEA levels in response to aggression in short‐ but not long‐day hamsters. Next, we experimentally induced adrenal DHEA release via injections of exogenous ACTH and assessed changes in aggressive behavior across photoperiods. We show a robust increase in aggression in short compared with long days during baseline aggression trials; however, aggression was not significantly increased further in response to ACTH in either photoperiod during post‐ACTH aggression trials. These findings suggest that DHEA plays a role in the regulation of short‐day aggression, while also highlighting the need for additional studies addressing the causal relationship between DHEA and aggression in this and others species. J. Exp. Zool. 9999A:XX–XX, 2015. © 2015 Wiley Periodicals, Inc.